Acoustic vowel analysis and speech intelligibility in young adult Hebrew speakers: Developmental dysarthria versus typical development. Issue 2 (1st February 2021) - Carl, Micalle; Icht, Michal
Abstract: Background: Developmental dysarthria is a motor speech impairment commonly characterized by varying levels of reduced speech intelligibility. The relationship between intelligibility deficits and acoustic vowel space among these individuals has long been noted in the literature, with evidence of vowel centralization (e.g., in English and Mandarin). However, the degree to which this centralization occurs and the intelligibility–acoustic relationship is maintained in different vowel systems has yet to be studied thoroughly. In comparison with American English, the Hebrew vowel system is significantly smaller, with a potentially smaller vowel space area, a factor that may impact upon the comparisons of the acoustic vowel space and its correlation with speech intelligibility. Data on vowel space and speech intelligibility are particularly limited for Hebrew speakers with motor speech disorders. Aims: To determine the nature and degree of vowel space centralization in Hebrew‐speaking adolescents and young adults with dysarthria, in comparison with typically developing (TD) peers, and to correlate these findings with speech intelligibility scores. Methods & Procedures: Adolescents and young adults with developmental dysarthria (secondary to cerebral palsy (CP) and other motor deficits, n = 17) and their TD peers ( n = 17) were recorded producing Hebrew corner vowels within single words. For intelligibility assessments, naïve listeners transcribed those words produced by speakers with CP, and intelligibility scores were calculated. Outcomes & Results: Acoustic analysis of vowel formants (F1, F2) revealed a centralization of vowel space among speakers with CP for all acoustic metrics of vowel formants, and mainly for the formant centralization ratio (FCR), in comparison with TD peers. Intelligibility scores were correlated strongly with the FCR metric for speakers with CP. Conclusions & Implications: The main results, vowel space centralization for speakers with CP in comparison with TD peers, echo previous cross‐linguistic results. The correlation of acoustic results with speech intelligibility carries clinical implications. Taken together, the results contribute to better characterization of the speech production deficit in Hebrew speakers with motor speech disorders. Furthermore, they may guide clinical decision‐making and intervention planning to improve speech intelligibility. What this paper adds What is already known on the subject: Speech production and intelligibility deficits among individuals with developmental dysarthria (e.g., secondary to CP) are well documented. These deficits have also been correlated with centralization of the acoustic vowel space, although primarily in English speakers. Little is known about the acoustic characteristics of vowels in Hebrew speakers with motor speech disorders, and whether correlations with speech intelligibility are maintained. What this paper adds to existing knowledge: This study is the first to describe the acoustic characteristics of vowel space in Hebrew‐speaking adolescents and young adults with developmental dysarthria. The results demonstrate a centralization of the acoustic vowel space in comparison with TD peers for all measures, as found in other languages. Correlation between acoustic measures and speech intelligibility scores were also documented. We discuss these results within the context of cross‐linguistic comparisons. What are the potential or actual clinical implications of this work?: The results confirm the use of objective acoustic measures in the assessment of individuals with motor speech disorders, providing such data for Hebrew‐speaking adolescents and young adults. These measures can be used to determine the nature and severity of the speech deficit across languages, may guide intervention planning, as well as measure the effectiveness of intelligibility‐based treatment programmes.